346. "Day after" high energy linear accelerator decomissioning: Characterization of the head of the accelerator. (December 2018) - Mariselli, M.; Ciarmatori, A.; Palleri, F.; Argazzi, E.; Lappi, S.; Belligotti, E.; Polisca, F.; Bunkheila, F.; Bono, M.
Abstract : Purpose: Italian laws are very restrictive in terms of release and exemption quantities in case of waste contaminated by radioactive isotopes. This study focuses on the characterization of a 18 MV Elekta Precise Linear Accelerator head that have been in clinical use since two days before its dismantling to make space to a new "state of the art" machine. Methods: Dismantling have been carried out by an Italian specialized company, each part of the machine have been first measured with a high efficiency α, β, γ contamination monitor equipped with ZnS:Ag detector and a portable γ-ray spectrometer (NaI(Tl)). Activated parts have been subsequently measured with a low background, high reliability and high definition spectrometric chain (DSA-1000 and Genie 2000 software, Canberra), with an electric cooled High Purity Germanium detector (HPGe) with 20% relative efficiency (GX2018 detector and Cryo-Pulse5 plus cooler, Canberra). Energy, FWHM and efficiency calibration have been performed with a multigamma Marinelli source in the range 59 keV ( 241 Am) – 1836 keV ( 88 Y). Efficiency curves for different geometries have been calculated with a 3D model of the detector-sample system and Montecarlo (MC) method by ISOCS/LabSOCS efficiency software (Canberra). Results: 57 Co, 58 Co, 60 Co, 54 Mn have been among the more frequent radioisotopes found. However short lived nuclides (eg. 122 Sb, 187 W, 57 Ni) were present as well. Conclusions: Activation of long lived radionuclides was confirmed as previously reported in published paper[1, 2] ; short lived radionuclides were detected as well. Waiting for full decay of short lived radioisotopes could allow to minimize the amount of radioactive waste.